Comparison of Murabahah and Musyarakah Financing in Home Ownership - Hammam, Syafiq Dzikrul; Bahri, Efri Syamsul (Yayasan Mitra Peduli Indonesia, 2025)
This study aims to compare the Murabahah and Musyarakah models regarding homeownership financing. This study uses a qualitative method with a descriptive, comparative, and literature study approach. The results of this study indicate that Murabahah and Musyarakah contracts can be used to finance home ownership. In-home financing using Murabahah and Musyarakah contracts has similarities, including the type of sharia financing. The Financial Accounting Standards Statement (PSAK) used is also included in the sharia standard. The difference between the two home financing contracts is that the Murabahah contract uses PSAK No. 102. Then the Musyarakah contract uses PSAK No. 106. The relationship between the bank and the customer in the Murabahah contract is between the seller and the buyer, while in the Musyarakah contract, it is a partnership. Installments in the Murabahah contract use fixed costs. Meanwhile, the Musyarakah contract will decrease from year to year. In the Murabahah contract, the house's value is the purchase price plus margin, while in the Musyarakah contract, it is according to the purchase price. The transfer of ownership rights in a Murabahah contract begins at the contract's start. In contrast, in a Musyarakah contract, the transfer of ownership rights is carried out in stages according to the installments.